Analisis Rencana Kerja, Perilaku Kerja, dan Komitmen Organisasi terhadap Kinerja Sekretariat DPRD - Bakar, Abu; Rusandy, Deby Satyo; Mulyanintyas, Ratna Dewi (Otonomi, 2026)
The increasing competitive demands on organizations in the era of globalization necessitate the availability of superior, intelligent, and highly motivated Human Resources (HR). In the context of local government, the Secretariat of the Regional House of Representatives (DPRD) of Kediri Regency plays a vital role as the facilitator for legislative, budgeting, and oversight functions. Therefore, the performance of its employees is exceedingly crucial and warrants investigation. This essential performance is presumed to be influenced by three main factors: the Work Plan, which serves as a strategic guide; Work Behavior, which reflects positive attitudes and actions in the workplace; and the level of employees' Organizational Commitment to the institution. This quantitative study aims to empirically examine and analyze how these three independent variables contribute to the employee performance at the Kediri Regency DPRD Secretariat, both simultaneously and partially. The research methodology employed is multiple regression analysis, with data collected through questionnaires administered to all employees. Based on the literature review, the proposed hypothesis suggests that the work plan, work behavior, and organizational commitment collectively and individually have a positive and significant influence on enhancing performance. The findings of this research are expected to provide academic contributions and practical recommendations for the leadership of the DPRD Secretariat to formulate policies focused on improving planning quality, cultivating an effective work culture, and strengthening employee loyalty and attachment.